A TTFV–pyrene-based copolymer: synthesis, redox properties, and aggregation behaviour. Issue 30 (4th March 2015) - Younes, Eyad A.; Williams, Kerry-Lynn M.; Walsh, Joshua C.; Schneider, Celine M.; Bodwell, Graham J.; Zhao, Yuming
Abstract : A new π-conjugated copolymer containing tetrathiafulvalene vinylogue and pyrene repeat units was synthesized and exhibited reversible redox activity, while the self-aggregation behaviour in the solution phase was responsive to external stimuli such as solvent and pH value. Abstract : A new π-conjugated copolymer having TTFV and pyrene repeat units was synthesized and found to exhibit reversible redox activity, while the self-aggregation behaviour in solution phase was found to be responsive to external stimuli (solvent and pH).